Aplikasi Kaidah Al-Umuru Bi Maqasidiha Dalam Aspek Ibadah - Zaviril, Yasmin Raihanah; Amanina, Pairuz; Siregar, Lulu Malona; Dinda; Hutabarat , Adinda Putri (Tabayyun : Journal Of Islamic Studies, 2025)
Qawaid al-Fiqhiyah has a strategic role in helping to formulate laws from problems that are not specifically explained in both the Quran and Hadith. This research aims to analyze the rule of Al-Umuru Bi Maqasidiha which relates to every word and action of the subject depending on the intention. the research method uses the literature study method as a data collection technique. The data collected is about how qawaidh fiqhiyyah is used as the basis for postulates in matters of worship. The results show that the rule of Al-Umuru Bi Maqasidiha is one of the fiqh rules that contains sharia law that a person in doing an act essentially has a certain purpose or intention. In terms of worship, a mukallaf must first intend to distinguish between acts of worship and deeds that have become habits in the surrounding environment.